Agent-Based Virtual Machine Migration for Load Balancing and Co-Resident Attack in Cloud Computing - Biao Xu; Minyan Lu (Applied Sciences, 2023)
The majority of cloud computing consists of servers with different configurations which host several virtual machines (VMs) with changing resource demands. Additionally, co-located VMs are vulnerable to co-resident attacks (CRA) in a networked environment. These two issues may cause uneven resource usage within the server and attacks on the service, leading to performance and security degradation. This paper presents an Agent-based VM migration solution that can balance the burden on commercially diverse servers and avoid potential co-resident attacks by utilizing VM live migrations. The Agent’s policies include the following: (i) a heuristic migration optimization policy to select the VMs to be migrated and the matching hosts; (ii) a migration trigger policy to determine whether the host needs to relocate the VMs; (iii) an acceptance policy to decide if the migration request should be accepted; and (iv) a balancer heuristic policy to make the initial VM allocation. The experiments and analyses demonstrate that the Agents can mitigate CRA in a distributed way to mitigate the associated risks while achieving acceptable load balancing performance.